Guium nebulum gen. et sp. nov., a New Cup Moth from Southern China Based on Morphological and Molecular Analysis (Lepidoptera: Zygaenoidea: Limacodidae) - Jun Wu; Ting-Ting Zhao; Hui Geng; Guang-Ze Jin; Hui-Lin Han (Insects)
A new genus and species of Limacodidae, Guium nebulum gen. et sp. nov., is described based on specimens collected from Guangxi Autonomous Region and Jiangxi Province in China. The new genus shares certain morphological features, such as a well-developed labial palpus, with related genera like Tanvia Solovyev & Witt, 2009; Scopelodes Westwood, 1841; Hyphorma Walker, 1865; and Monema Walker, 1855. However, the new genus can be separated from them by the wing venation and the male genital characteristics. COI molecular marker analysis further supports the monophyly of this new genus, indicating a close relationship with Scopelodes.